2020
DOI: 10.1039/d0cc05876a
|View full text |Cite
|
Sign up to set email alerts
|

The latest development of CoOOH two-dimensional materials used as OER catalysts

Abstract: The electrocatalytic water splitting, which is driven by renewable energy input to produce oxygen, has been widely regarded as a promising strategy in the future energy portfolio. The two-dimensional structure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 70 publications
1
42
0
Order By: Relevance
“…Moreover, as seen from the Co K ‐edge FT‐EXAFS curves in Figure 5 b, an emerging peak located at around 2.35 Å, assigned to the contributions of Co‐Co/Cu bonds, is clearly observed for CoCu‐MOF NBs after the OER operation, compared with the initial one [26, 40] . Interestingly, both the Co K ‐edge k 2 χ( k ) oscillation and FT‐EXAFS curves of CoCu‐MOF NBs after the OER closely resemble to those of the γ‐CoOOH reference (Figure 5 a,b), indicating the formation of Co‐based oxyhydroxide analogue during the OER [40, 41] . More importantly, the Cu K ‐edge k 2 χ( k ) oscillation and FT‐EXAFS curves of CoCu‐MOF NBs after OER look very similar to that at Co K ‐edge (Figure S22, Supporting Information), which infers resembled structural configurations of Co and Cu sites in CoCu‐MOF NBs after OER.…”
Section: Figurementioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, as seen from the Co K ‐edge FT‐EXAFS curves in Figure 5 b, an emerging peak located at around 2.35 Å, assigned to the contributions of Co‐Co/Cu bonds, is clearly observed for CoCu‐MOF NBs after the OER operation, compared with the initial one [26, 40] . Interestingly, both the Co K ‐edge k 2 χ( k ) oscillation and FT‐EXAFS curves of CoCu‐MOF NBs after the OER closely resemble to those of the γ‐CoOOH reference (Figure 5 a,b), indicating the formation of Co‐based oxyhydroxide analogue during the OER [40, 41] . More importantly, the Cu K ‐edge k 2 χ( k ) oscillation and FT‐EXAFS curves of CoCu‐MOF NBs after OER look very similar to that at Co K ‐edge (Figure S22, Supporting Information), which infers resembled structural configurations of Co and Cu sites in CoCu‐MOF NBs after OER.…”
Section: Figurementioning
confidence: 72%
“…This downshifting of metal d band center, induced by the Cu atom incorporation, could properly weaken the strong oxo‐species affinity of CoOOH, and then effectively balance the adsorption energetics of key intermediates toward fast OER kinetics for CoCuOOH. As illustrated by the Gibbs free energy changes in Figure 5 f, the formation of *OOH intermediate over Co sites of CoOOH has the largest thermodynamic barrier of 1.80 eV during the OER process, which indicates the O−O bond coupling is the OER rate‐determining step [41, 42] . Notably, the free energy change of *OOH intermediate formation is reduced to 1.68 eV for CoCuOOH after the Cu atom incorporation, which is responsible for the great promotion in the OER kinetics.…”
Section: Figurementioning
confidence: 95%
“…[26,40] Interestingly, both the Co K-edge k 2 c(k) oscillation and FT-EXAFS curves of CoCu-MOF NBs after the OER closely resemble to those of the g-CoOOH reference (Figure 5 a,b), indicating the formation of Cobased oxyhydroxide analogue during the OER. [40,41] More importantly, the Cu K-edge k 2 c(k) oscillation and FT-EXAFS curves of CoCu-MOF NBs after OER look very similar to that at Co K-edge (Figure S22 [18,[42][43][44] Indeed, after the Cu atom incorporation, the d band centre of CoCuOOH has been greatly downshifted from À2.10 to À2.62 eV relative to CoOOH (Figure S25a,b, Supporting Information). It has been demonstrated that pure CoOOH usually shows moderate OER activity due to the excessively strong binding ability with oxo-intermediates during the oxygen catalytic process.…”
mentioning
confidence: 77%
“…As illustrated by the Gibbs free energy changes in Figure 5 f, the formation of *OOH intermediate over Co sites of CoOOH has the largest thermodynamic barrier of 1.80 eV during the OER process, which indicates the O À O bond coupling is the OER ratedetermining step. [41,42] Notably, the free energy change of *OOH intermediate formation is reduced to 1.68 eV for CoCuOOH after the Cu atom incorporation, which is responsible for the great promotion in the OER kinetics. It is also noteworthy that, for CoCuOOH, the Gibbs free energy change of *OOH generation over Co sites is much lower than that on Cu sites (2.15 eV; Figure S25c, Supporting Information), which may demonstrate Co sites are the real OER active sites in CoCuOOH.…”
mentioning
confidence: 99%
“…Inactive and low-cost materials as potential catalysts should be activated as high-performance OER electrocatalysts. In situ-generated active species (e.g., Co 3+ oxyhydroxides) after surface reconstruction can serve as main active sites, offering high activity capabilities [ 55 , 62 , 86 , 116 ]. The challenge is how rationally and precisely to initiate the surface reconstruction of inactive catalysts.…”
Section: Accelerating Surface Reconstructionmentioning
confidence: 99%